The experience of Russia, the USA, Germany, France, and China in improving the activities of auxiliary enterprises in military units (International conference on multidisciplinary science, 2023)
this article examines the experience of foreign countries in improving the activities of auxiliary farms in military units. In addition, the role and importance of the military industrial complex in the development of the military sector is highlighted. In particular, the experience of Russia and the USA, as well as information on the article from leading countries such as Germany, France, and China are presented.